Grimms' fairy tales - Grimm, Jacob Ludwig Karl, 1785-1863; Grimm, Wilhelm, 1786-1859 (London : HarperPress, 2013)
HarperCollins is proud to present its new range of best-loved, essential classics.
Translation of: Kinder- und Hausmärchen
Keywords: Fairy tales -- Germany